2018
DOI: 10.1159/000497351
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus in Thai Women and Men with Anogenital Warts

Abstract: Objective: Anogenital warts are caused by human papillomavirus (HPV). Globally, HPV genotypes 6 and 11 are most often associated with anogenital warts. However, the diversity of HPV genotypes found in patients with genital warts in Thailand is unknown. The aim of this study was to investigate HPV-associated anogenital warts in the Thai population and to assess whether genotypes found are represented in the bivalent and quadrivalent HPV vaccine. Methods: This study included 206 anogenital swab samples from pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
(40 reference statements)
2
5
0
Order By: Relevance
“…The rate of HPV infection in the participants with EGL (67.79%) was similar to that reported in other studies (72.3% in Brazil, 61.3% in the USA, and 61.9% in Mexico - HIM Study), but lower than the results obtained in Thailand (88.3%), Turkey (75.8%), Colombia (88.9%), China (97.0%) and Ireland (78%) [ 13 , 14 , 33 – 36 ]. The discrepancy between these results could be due to differences in the sampling techniques or methods, misdiagnoses or true differences among the populations.…”
Section: Discussionsupporting
confidence: 88%
“…The rate of HPV infection in the participants with EGL (67.79%) was similar to that reported in other studies (72.3% in Brazil, 61.3% in the USA, and 61.9% in Mexico - HIM Study), but lower than the results obtained in Thailand (88.3%), Turkey (75.8%), Colombia (88.9%), China (97.0%) and Ireland (78%) [ 13 , 14 , 33 – 36 ]. The discrepancy between these results could be due to differences in the sampling techniques or methods, misdiagnoses or true differences among the populations.…”
Section: Discussionsupporting
confidence: 88%
“…is result is consistent with the previous studies in ailand, the United States, Brazil, Mexico, and China [17][18][19][20]. We also found that coinfections with multiple types of HPV were frequent, which is in agreement with prior studies [21].…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous studies, we used anal exfoliated cells to assess HPV infection in CA patients as in previous studies 31,32 . HPV infection in the anal region can be more comprehensively reflected by wiping CA lesions and anal canal.…”
Section: Discussionmentioning
confidence: 82%
“…Path analysis of the influencing factors for oncogenic HPV, HPV16, HPV52 infection among patients with anal CA (Table 5 and Consistent with previous studies, we used anal exfoliated cells to assess HPV infection in CA patients as in previous studies. 31,32 HPV infection in the anal region can be more comprehensively reflected by wiping CA lesions and anal canal. Multi-site sampling can promote more infections to be detected, which is beneficial to provide a basis for further exploring the risk factors of carcinogenic HPV infection.…”
Section: Sem Of Influencing Factors For Oncogenic Hpv Hpv16 Hpv52 Inf...mentioning
confidence: 99%